Ghosting Reciprocity in Recruitment: A Conceptual Study of Candidate Ghosting in Generation Z Job Applicants - Sri Yuni Astuti T (CV Edujavare Publishing, 2026)
This study aims to analyze the phenomenon of candidate ghosting in Generation Z through a conceptual literature review approach by integrating the perspectives of candidate experience, employer ghosting, digital social proof, and Social Exchange Theory. The research uses the conceptual literature review method by examining various relevant scientific literature regarding recruitment behavior, candidate experience, Generation Z characteristics, recruitment communication, and social relations in organizations. Analysis is carried out through the process of identification, classification, synthesis, and interpretation of various research findings to build a more comprehensive conceptual understanding. The results of the synthesis show that candidate ghosting cannot be understood solely as a form of candidate unprofessionalism, but rather as a phenomenon influenced by the communication experience received during the recruitment process. The practice of employer ghosting, changes in Generation Z's expectations for transparency and speed of communication, and the influence of digital social proof contribute to the formation of candidate perceptions and behaviors in recruitment relationships. This research offers the concept of ghosting reciprocity as a conceptual framework that explains that candidate ghosting can emerge as a form of negative reciprocity that develops from previous communication experiences with the organization. These findings underscore the importance of a more transparent, responsive, and experience-oriented recruitment process to minimize ghosting from both parties.